Estratégias reprodutivas de espécies de Astyanax do baixo Rio Iguaçu Paraná, Brasil - Machado, Fabiana Simões (2016)
The richness and abundance of Astyanax in the Iguaçu River basin, suggests that this genre has succeeded in colonizing the region. However, one of the attributes of life strategies of a population that influence the success of the colonization of an environment is the reproductive strategy adopted by the species. The aim of this study was to determine some aspects of the reproductive biology of the genus Astyanax species in the stretch between the dams downstream Salto Caxias the mouth of the San Antonio River delineated in the lower Rio Iguaçu, relating them to the precipitation for the study period. For that were established 25 sampling points being conducted monthly collections September / 2013 to August / 2014. Using gill nets (2.5 to 14 cm between the nodes affixed); sorceress (6.0; 7.0; 8.0 cm) and electric fishing; exposed for 24 hours with revised every 6 hours. Regarding reproductive parameters was analyzed monthly sex ratio, tested by chi-square test (X²); frequency of occurrence of gonadal development stages, the average monthly values of gonadosomatic relationship, reproductive activity Index (IAR) for environment and precipitation for the months of study. It was captured and analyzed a total of 9,016 individuals of Astyanax in the sampled area. The species with greater capture was Astyanax bifasciatus (4,151 individuals, 60.6% females and 39.8% males), followed by Astyanax gymnodontus (1,633 individuals, 67.9% females and 32% males), Astyanax minor (1.386 individuals, 61.9% females and 38% males), Astyanax altiparanae (1,288 individuals, 68% females and 31.9% males), Astyanax dissimilis (545 individuals, 66.4% females and 33.5% males) and Astyanax gymnogenys (13 individuals, 53.8% females and 46.1% males). The sex ratio showed a predominance of females in almost every month of the year for the species. The frequency of gonadal development stages and the average monthly gonadosomatic relationship indicated that the species have reproductive activity throughout the year, being higher for the months when rainfall was more abundant. The values of IAR> 20 obtained for the species of the genus Astyanax in environments show a preference for tributary as spawning environments.